2003
DOI: 10.1097/01.cpm.0000080906.11193.b5
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of Reintubation of Mechanically Ventilated Patients

Abstract: About 15% of long-term mechanically ventilated patients who are removed from mechanical ventilation and extubated require reintubation within 48-72 hours after extubation. The reasons for reintubation can be divided in two groups: reintubation because of either upper airway obstruction or respiratory distress. Some authors have associated reintubation with a higher incidence of ventilator-associated pneumonia and a higher mortality. Studies that have analyzed mortality observed different outcomes depending upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
2
13
0
5
Order By: Relevance
“…5,11,21,23 In the same way, we observed that in the postoperative phase following elective intracranial surgery, our patients who were reintubated spent longer times on of mechanical ventilation (P < 0.0001), remained in the ICU for longer times (P < 0.0001), had longer hospital stays (P < 0.0001) and presented higher incidence of respiratory complications (P < 0.0001).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…5,11,21,23 In the same way, we observed that in the postoperative phase following elective intracranial surgery, our patients who were reintubated spent longer times on of mechanical ventilation (P < 0.0001), remained in the ICU for longer times (P < 0.0001), had longer hospital stays (P < 0.0001) and presented higher incidence of respiratory complications (P < 0.0001).…”
Section: Resultssupporting
confidence: 71%
“…8,9,18,[20][21][22][23] Nevertheless, we found that a lowered level of consciousness was the main cause of postoperative reintubation following elective intracranial surgery (71.5%). This may relate to the surgical procedure or to another factor relating to the respiratory center consequent to surgical manipulation, which would be likely to lead to hypoventilation and consequent CO 2 elevation, along with a drop in the level of consciousness.…”
Section: Resultsmentioning
confidence: 99%
“…29 ICU-acquired weakness during mechanical ventilation causes deterioration of global muscle strength, tetraparesis, and reduced respiratory muscle strength, leading to longer mechanical ventilation and failed weaning and extubation. 30 The subjects in this study showed an overall reduction in muscle strength, evidenced in the upper (grade 3) and lower (grade 2) limbs.…”
Section: Discussionmentioning
confidence: 58%
“…40 The main cause of extubation failure is the development of respiratory failure within a few hours. Noninvasive positive-pressure ventilation has been evaluated in the prevention and management of this condition.…”
Section: Noninvasive Ventilation For Prevention Of Respiratory Failurementioning
confidence: 99%